228k views
3 votes
Solve the following equation:
(n + 1) + 3(n - 1) = 2(n - 1)(n + 1)​

User OpenGG
by
5.4k points

1 Answer

5 votes

Answer:

n = 0, n =2

Explanation:

Given

(n + 1) + 3(n - 1) = 2(n - 1)(n + 1) ← distribute parenthesis on both sides

n + 1 + 3n - 3 = 2(n² - 1), that is

4n - 2 = 2n² - 2 ( subtract 4n - 2 from both sides )

0 = 2n² - 4n ← factor out 2n from each term )

0 = 2n(n - 2)

Equate each factor to zero and solve for n

2n = 0 ⇒ n = 0

n - 2 = 0 ⇒ n = 2

User Dyaniyal Wilson
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.